Penyesuaian Diri Anak Asuh di Lembaga Kesejahteraan Sosial Anak (LKSA) - M. Youri Alkayyis; Dwi Yuliani; Windriyati Windriyati (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
Self-adjustment refers to the suitability of individual behavior, so that there is a harmonious relationship between himself and the environment. This study aims to obtain an empirical picture of: 1) characteristics of foster children, 2) adaptation of foster children to the natural environment, 3) adaptation of foster children to the social environment, 4) adaptation of foster children to themselves, and 5) the adaptation of foster children to the tensions, conflicts and frustrations they experience at the Child Welfare Institution (CWI). The method used in this research is secondary data analysis. The number of respondents was 417 foster children consisting of ages 6-21 years in the following six locations: 1) Bina Remaja Taruna Jaya Social Institution in South Jakarta, 2) XVII Youth Inabah Pondok Putri Suryalaya Islamic Boarding School in Ciamis, 3) Putra Putra Primary 5 Children's Orphanage in East Jakarta, 4) The Muhammadiyah Orphanage in Klaten, 5) Marsudi Putra Antasena Social Home in Magelang, and 6) Baiturahmah Orphanage in Kampar, Riau. The data collection technique used is secondary data analysis. Data analysis techniques used are the reduction and categorization of data, organizing data, and interpretation. The results showed that the adaptation of foster children to the natural environment showed a high category, adjustment to the social environment shows a low category because there are still many foster children who do not have a good relationship with other foster children, coaches and employees/staff, adjustment to themselves shows a low category because foster children find it difficult to control emotions and cannot focus on participating in activities at the Child Welfare Institution (CWI), adjusting to the tension, conflict and frustration they experienced showed a moderate category.